NILAI-NILAI PENDIDIKAN KARAKTER DALAM DONGENG DOMBA DAN SAHABAT RIMBA KARYA KAK THIFA SEBAGAI ALTERNATIF BAHAN AJAR PESERTA DIDIK KELAS II SEKOLAH DASAR - Dwi Apriliani, Denisya; Nurdianasari, Nindya; Darmayanti, Vivi; Badrus Sholeh Arif, Moh; Cahyanto, Bagus (EduStream: Jurnal Pendidikan Dasar, 2023)
The high number of cases of violence and bullying that occur is a character crisis or the fading of character values in children. These challenges and problems are easy to face if children have good character values from various aspects through character education. The purpose of this research is to describe the character values that exist in fables, describe the use of fables as an alternative teaching material in elementary schools, and describe the efforts that can be implemented to instill character education values. This type of research is descriptive research. This study uses the qualitative data analysis technique of Miles and Hibermas. The results of the study show that there are 13 character education values in the book “Fairy Tales of Sheep and Friends of the Jungle” by Kak Thifa. Fairy tale books can be used as an alternative teaching material for second grade elementary school students in the form of worksheets. Efforts or methods made by IIC SD class teachers in instilling character education can be done in various ways, namely through exemplary, collaborative and active learning in the classroom, stories and literature, character assessment or reflection, advice and punishment, and giving motivation. Based on the results of the study, it can be concluded that there are 13 character education values in the book "Tale of the Sheep and Friends of the Jungle" by Kak Thifa. Fairy tales can be used as an alternative teaching material for second grade elementary school students as well as the efforts or methods carried out by teachers in instilling character education can be done in various ways.